2021
DOI: 10.1038/s41467-021-24930-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxin import through the antibiotic efflux channel TolC

Abstract: Bacteria often secrete diffusible protein toxins (bacteriocins) to kill bystander cells during interbacterial competition. Here, we use biochemical, biophysical and structural analyses to show how a bacteriocin exploits TolC, a major outer-membrane antibiotic efflux channel in Gram-negative bacteria, to transport itself across the outer membrane of target cells. Klebicin C (KlebC), a rRNase toxin produced by Klebsiella pneumoniae, binds TolC of a related species (K. quasipneumoniae) with high affinity through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…ARGs enrichments in human-intervened mangroves could lead to accelerated ARGs dissemination among microbes of different phylogeny through horizontal gene transfer ( Laroche et al, 2009 ; Imchen and Kumavath, 2020 ). The most abundant genes were outer membrane proteins such as TolC, which is a major outer-membrane antibiotic efflux channel in Gram-negative bacteria ( Housden et al, 2021 ); and regulatory proteins that form part of two-component system such as FleR, which is part of FleS–FleR system and has a role in intrinsic antibiotic resistance ( Gooderham and Hancock, 2009 ), or AtoC involved in resistance to aminoglycoside antibiotics through AtoC-AtoS system ( Matta et al, 2007 ; Supplementary Tables 1 – 4 ). In the case of El Palmar, the lower exposure to antibiotics results in lower gene richness and lower gene diversity ( Table 2 and Supplementary Figure 1 ), which would seem to indicate that in pristine sites the diversity of ARGs is low.…”
Section: Discussionmentioning
confidence: 99%
“…ARGs enrichments in human-intervened mangroves could lead to accelerated ARGs dissemination among microbes of different phylogeny through horizontal gene transfer ( Laroche et al, 2009 ; Imchen and Kumavath, 2020 ). The most abundant genes were outer membrane proteins such as TolC, which is a major outer-membrane antibiotic efflux channel in Gram-negative bacteria ( Housden et al, 2021 ); and regulatory proteins that form part of two-component system such as FleR, which is part of FleS–FleR system and has a role in intrinsic antibiotic resistance ( Gooderham and Hancock, 2009 ), or AtoC involved in resistance to aminoglycoside antibiotics through AtoC-AtoS system ( Matta et al, 2007 ; Supplementary Tables 1 – 4 ). In the case of El Palmar, the lower exposure to antibiotics results in lower gene richness and lower gene diversity ( Table 2 and Supplementary Figure 1 ), which would seem to indicate that in pristine sites the diversity of ARGs is low.…”
Section: Discussionmentioning
confidence: 99%
“…After a transient period, growth at the colony surface is restored, and expression of resistance is resumed among growing cells at the colony surface. Unlike nutrients, active import of antibiotics is at least very rare ( Delcour, 2009 ; Sugano et al, 2010 ; Housden et al, 2021 ; Rybenkov et al, 2021 ). In our case, tetracycline diffuses slowly through the cell membrane, with a half-equilibration time of approximately 45 min ( Sigler et al, 2000 ; Reuter et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Shortly after this work was made available, a similar structure demonstrated that KlebC, a rRNAse bacteriocin from Klebsiella pneumoniae , binds TolC from Klebsiella quasipneumoniae with a binding mode similar to that of ColE1 binding TolC ( Housden et al, 2021 ). KlebC is closed in the unbound state as confirmed by the high-resolution X-ray crystal structure, which supports our proposed conformation ( Figure 2E ), and opens into a single-pass, kinked-helix to bind to TolC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, E. coli exposure to TolC-box-containing peptides can prevent subsequent binding and cytotoxicity of full-length colicin E1 ( Jakes, 2017 ). CD of the T domain indicates that it exists as a helical hairpin (closed hinge) in solution similar to other colicin T domains ( Wiener et al, 1997 ; Housden et al, 2021 ) and that the proline at the center of the TolC box forms its apex ( Zakharov et al, 2016 ; Housden et al, 2021 ). This measurement led to the proposal, known as the ‘pillar model,’ ( Zakharov et al, 2016 ) that the T domain inserts into the TolC barrel as a helical hairpin where the N and C-termini are pointing to the cell exterior.…”
Section: Introductionmentioning
confidence: 88%